Managing the Lower Eyelid Complex in the Thick-Skinned Patient - Floyd, Elizabeth Mia; Perkins, Stephen W. (Facial Plastic Surgery, 2018)
Thick skin presents a unique set of challenges within the realm of facial plastic surgery, and addressing the lower lid complex is no exception. There are several procedures for addressing the lower lids, the first and foremost being lower lid blepharoplasty. However, the remaining procedures combined with surgical techniques have exclusive implications in thick skin. Understanding the anatomy and various techniques that can be applied to thick skin can help achieve aesthetically more pleasing results in comparison to those of thin skin. As will be discussed in this article, patients with skin color of Fitzpatrick's grade III or higher have several characteristics associated with their skin, including thicker dermis as well as different patterns of aging, which have implications for addressing the lower lid complex. The senior author has extensive experience performing lower lid procedures and seeks to impart how best to understand and adapt for these differences to allow for the best aesthetic result.
Keywords: lower lid blepharoplasty; thick skin; periorbital rejuvenation; canthoplasty; canthopexy